Pre-service teachers’ attitudes toward citizenship education in Israel - Zvulun, Jacky Yaakov; Gindi, Shahar (JSSE - Journal of Social Science Education, 2024)
Highlights: Civic education in Israel is used as a political tool, neglecting broader citizenship education. Study examines attitudes of 235 pre-service teachers (PSTs) towards citizenship education. PSTs value citizenship education but are confused about teaching methods, goals, and implementation. Factors contributing to confusion: resistance to citizenship education, fear of political issues, and curriculum pressure. Emphasizes the need for comprehensive citizenship education across schooling levels, fostering active democratic citizenship. Purpose: Reviewing civic education in Israel reveals that it has been used as a political tool, while the broader field of citizenship education has hardly been examined. This study addresses the gap in the literature regarding PSTs’ (PSTs’) attitudes towards citizenship education. Methodology: Questionnaires among 235 PSTs in two colleges were used to examine the significance and value of citizenship education in Israel. Findings: PSTs recognised the importance of citizenship education but also conveyed confusion regarding teaching methods, long-term goals, and curriculum implementation. This confusion may stem from a reluctance to integrate citizenship education into various subjects, fear of addressing political issues, and pressure from curriculum guidelines. Research implications: The study emphasises the need for an expanded focus on citizenship education in educational institutions and the integration of citizenship education across different levels of schooling, which can equip students with the knowledge, values, and skills necessary for active citizenship in a democratic society.